2019
DOI: 10.1108/cg-03-2018-0111
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance integration with sustainability: a systematic literature review

Abstract: Purpose The purpose of this paper is to systematically review the literature on corporate governance and sustainability integration in identifying the main rigidity, infirmity and gaps in the current literature, and also to mention future research paths. Design/methodology/approach A systematic literature review of existing international papers is used through quantitative and qualitative approach by selecting 27 articles published in Scopus. Findings The review suggests although integration of governance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 64 publications
0
35
0
1
Order By: Relevance
“…To offer insights and critique that evaluate, identify and address possible future research agendas for AAOIFI, we adopt the systematic literature review. This methodology is inspired by the previous studies (E-Vahdati et al , 2019; Le et al , 2019; Nomran and Haron, 2020). This method takes into consideration the AAOIFI standards’ issues as compared with other standards, along with their importance, necessity to adopt, measuring level of compliance, determinants and consequences.…”
Section: Methodsmentioning
confidence: 99%
“…To offer insights and critique that evaluate, identify and address possible future research agendas for AAOIFI, we adopt the systematic literature review. This methodology is inspired by the previous studies (E-Vahdati et al , 2019; Le et al , 2019; Nomran and Haron, 2020). This method takes into consideration the AAOIFI standards’ issues as compared with other standards, along with their importance, necessity to adopt, measuring level of compliance, determinants and consequences.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, our results are in line with those found by previous works (Kang et al , 2010; Majeed et al , 2015; Trireksani and Djajadikerta, 2016). We can explain the existence of a positive relationship between these two variables by the fact that the issue of corporate governance and its integration into the concept of sustainability and environmental performance has recently attracted increasing interest (E-Vahdati et al , 2019). Our results are in line with those of De la Cuesta and Valor (2013), Galbreath (2013), as well as Kolk and Pinkse (2010), who found that good corporate governance practices play a central role in integrating environmental and social goals into decision-making.…”
Section: Empirical Tests and Findingsmentioning
confidence: 99%
“…Vision and mission (including strategies) are one of the most discussed governance factors, which are used guidance in decision-making and daily business (Kiesnere and Baumgartner, 2019). Vision and mission statements are effective for establishment of sustainability structure (E- Vahdati et al, 2019). An organisation should include sustainability in its vision and mission to make it an integral part of the organisation's policies (Hahn, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The person in charge, also referred to as champion (Niedlich et al, 2020), can influence an organisation's success (Sánchez et al, 2020), help to create a clearer sustainable structure (E- Vahdati et al, 2019), and promote the organisation commitment to sustainability (Krechovská and Procházková, 2014), especially when working closely with leadership (Lozano, 2006;Mader et al, 2013;Bauer et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%